Effective access to health services: operationalizing universal health coverage - Germán Fajardo-Dolci; Juan Pablo Gutiérrez; Sebastián García-Saisó (Instituto Nacional de Salud Pública, 2015)
The right to health and its operational form, as an organized social response to health: the right to health protection, are the mainstay for the global push towards universal health coverage. The path to achieve this goal is particular to each country and relates to the baseline and specific context in relation to what is feasible. In practical terms, universal coverage involves the correlation between demand and supply of services (promotion, prevention, and care), expressed by the ability for each individual to make use of services when these are required. In those terms universal coverage is then effective access. The objective of the paper is to explore the conceptualization of effective access to health services and propose a definition that allows its operationalization thereof. This definition considers key elements of supply and demand of services, including the availability of resources and adequate provision (quality), as well as barriers to use them.